2021
DOI: 10.1158/1078-0432.ccr-21-0327
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Pembrolizumab for the Treatment of Tumor Mutational Burden–High Solid Tumors

Abstract: The FDA approved pembrolizumab on June 16, 2020, for the treatment of adult and pediatric patients with unresectable or metastatic tumor mutational burden–high [TMB-H; ≥10 mutations/megabase (mut/Mb)] solid tumors, as determined by an FDA-approved test, that have progressed following prior treatment and who have no satisfactory alternative treatment options. FDA granted the approval based on a clinically important overall response rate (29%; 95% confidence interval, 21–39) and duration of response (57% of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(208 citation statements)
references
References 18 publications
2
169
0
1
Order By: Relevance
“…Based on these features, it is indicated that LUAD patients with high NMGs signature may benefit more from immune checkpoint inhibitors (Lucibello et al, 2021). In concordance with a more inflamed tumor microenvironment, tumor mutation counts (also known as tumor mutation burden, TMB) level was significantly higher in the high NMGs signature than in the low group, which has already been granted as an effective biomarker for selecting patients who may respond to pembrolizumab by FDA (Marcus et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Based on these features, it is indicated that LUAD patients with high NMGs signature may benefit more from immune checkpoint inhibitors (Lucibello et al, 2021). In concordance with a more inflamed tumor microenvironment, tumor mutation counts (also known as tumor mutation burden, TMB) level was significantly higher in the high NMGs signature than in the low group, which has already been granted as an effective biomarker for selecting patients who may respond to pembrolizumab by FDA (Marcus et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Mutational load was defined as the sum of silent and non-silent mutations per megabase (Mb). Using the recently FDA-approved cut-off of 10 mutations per megabase (mut/Mb), the tumors were categorized into a TMB-low (TMB-L, ≤10 mut/Mb) and a TMB-high (TMB-L, >10 mut/Mb) group for further analysis [ 39 ]. As a genomic classifier in the CPTAC validation cohort, we analyzed synonymous and non-synonymous single nucleotide variants (SNV).…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, FDA approved PD-1 antibody pembrolizumab for the treatment of TMB-H (TMB >10 mutations/megabase) solid tumors. This approval was based on the results of the KEYNOTE-158 trial ( Marcus et al, 2021 ). Pembrolizumab achieved an overall response rate (ORR) of 29% in TMB-H patients (13%, n = 102).…”
Section: Discussionmentioning
confidence: 99%